2017
DOI: 10.14429/djlit.37.5.11090
|View full text |Cite
|
Sign up to set email alerts
|

Use of WhatsApp for Effective Delivery of Library and Information Services

Abstract: <div class="page" title="Page 1"><div class="layoutArea"><div class="column"><p><span>Information communication technology playing a major role in transmitting idea, thought and information between one to another. Social networking websites are a good example of communication network and it is a social structure that lets the user interact and work collaboratively with other users. WhatsApp is a free instant </span><span>messenger application that allows users to send … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…WhatsApp is also used as a source of news and information [Ansari and Tripathi, 2017]. As an outcome of ISP discussions, a private Facebook group was also created for information sharing post-ISP.…”
Section: Social Media For Sustained Communicationmentioning
confidence: 99%
“…WhatsApp is also used as a source of news and information [Ansari and Tripathi, 2017]. As an outcome of ISP discussions, a private Facebook group was also created for information sharing post-ISP.…”
Section: Social Media For Sustained Communicationmentioning
confidence: 99%
“…Several previous studies regarding the use of WhatsApp for instance explore the role of WhatsApp in interactions between consumers and companies [22], WhatsApp as a communication medium [4] and learning exchange [23] as well as study on the ability of WhatsApp application to disseminate information to become "viral" [24] and making it as a marketing tool [14]. WhatsApp as social media could also be used as a gathering place (group) and can be used to spread information [25] with one click to many people (broadcast message) so that it becomes an effective advertising medium [26] and coordinating information trade [27]. However, although a lot of research has been done on WhatsApp, research on using WhatsApp as a marketing communication medium has not yet been found.…”
Section: Introductionmentioning
confidence: 99%
“…Background to the study WhatsApp is an encrypted instantaneous messaging application that was developed by Brian Acton and Jan Koum in 2009 (Anderson, 2016) but owned by Facebook since 2014 (Ansari and Tripathi, 2017). It is an Internet-based application available for both personal computer (PC) and smartphones that is capable of sending text messages, multimedia messages, documents, audio messages, images, contacts and user location to other users.…”
mentioning
confidence: 99%
“…The popularity of WhatsApp, more especially amongst the younger generation (Nyasulu and Chawinga, 2019), makes it an ideal platform for providing library services. Moreover, Ansari and Tripathi (2017) discovered that users' attitudes towards the use of WhatsApp in providing library services are favourable as they view it as a vehicle for the provision of better services. There is also evidence that WhatsApp is increasingly being deployed in libraries.…”
mentioning
confidence: 99%
See 1 more Smart Citation